Biochar of hazelnut shell mitigates cadmium toxicity in forage soybean - Severoğlu, Sedat; Karabacak, Tuba; Yazıcı, Abdullah; Aktaş, Halit; Çerit, Nilay; Ekinci, Melek; Güllap, Mehmet Kerim; Turan, Metin; Yildirim, Ertan (Frontiers in Plant Science, 2025)
Cadmium (Cd) contamination threatens plant growth by disrupting physiological and biochemical processes, leading to reduced biomass and nutrient imbalances. Biochar, a carbon-rich byproduct of pyrolysis, has gained attention for its ability to improve soil properties and mitigate heavy metal toxicity, enhancing plant resilience. This study examines biochar’s role in alleviating Cd stress in forage soybean (Glycine max L. Merrill), focusing on its effects on growth, nutrient uptake, antioxidant enzyme activities, and phytohormone regulation. A greenhouse experiment was conducted using two biochar levels (B0: Control, B1: 3% biochar) and four Cd concentrations (Cd0: Control, Cd1: 50 mg kg-1, Cd2: 100 mg kg-1 and Cd3: 200 mg kg-1) in a 2 × 4 factorial design with three replications. Biochar and Cd were applied to mixtures consisting of soil (loamy), sand, and peat (3:1:1, v:v:v). Growth parameters, mineral content, antioxidant enzyme activities (catalase-CAT, peroxidase-POD and superoxide dismutase-SOD), and stress indicators (hydrogen peroxide H2O2, malondialdehyde-MDA, proline and sucrose) were analyzed. Key phytohormones, including abscisic acid-ABA, indole acetic acid-IAA, gibberellic acid-GA, salicylic acid-SA, cytokinin and jasmonic acid-JA, were measured. Cd stress reduced plant growth and nutrient content while increasing oxidative stress markers and antioxidant enzyme activity. Compared to the B0Cd0 treatment, the B0Cd1, B0Cd2, and B0Cd3 treatments resulted in 45, 62 and 67% decrease in shoot fresh weight (SFW), 37, 46 and 50% decrease in shoot dry weight (SDW), 31, 45 and 56% in root fresh weight (RFW), 34, 50 and 59% in root dry weight (RDW), and 13, 29 and 40% de-crease in LA. Biochar mitigated these negative effects by enhancing growth, nutrient assimilation, and biochemical responses. Under Cd stress, biochar reduced H2O2, MDA, proline and sucrose accumulation, and modulated enzymatic activities, improving stress tolerance in soybean plants. Based on these findings, it is thought that hazelnut shell biochar can effectively alleviate Cd-induced stress in forage soybean by promoting growth, nutrient uptake, and biochemical stability. However, further studies are recommended to explore the use of hazelnut shell biochar as a sustainable soil amendment for reducing heavy metal toxicity in agricultural systems.